Association of branched-chain amino acids with mortality-the Ludwigshafen Risk and Cardiovascular Health (LURIC) study - Moissl-Blanke, Angela P.; Lorkowski, Stefan; Meinitzer, Andreas; Pilz, Stefan; Scharnagl, Hubert; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Krämer, Bernhard; Pieske, Burkert; Grübler, Martin R.; Brussee, Helmut; von Lewinski, Dirk; et al. (iScience, 2023)
Branched-chain amino acids (BCAAs) are effectors of metabolic diseases, but their impact on mortality is largely unknown. We investigated the association of BCAA with risk factors and mortality in 2,236 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study using linear and Cox regression. Adiponectin, hemoglobin, C-peptide, hemoglobin A1c, and homoarginine showed the strongest association with BCAA concentration (all p < 0.001). During a median follow-up of 10.5 years, 715 participants died, including 450 cardiovascular-related deaths. BCAA concentrations were inversely associated with the risk of all-cause and cardiovascular mortality (HR [95% CI] per 1-SD increase in log-BCAA: 0.75 [0.69-0.82] and 0.72 [0.65-0.80], respectively) after adjustment for potential confounders. BCAAs are directly associated with metabolic risk but inversely with mortality in persons with intermediate-to-high cardiovascular risk. Further studies are warranted to evaluate the diagnostic and therapeutic utility of BCAA in the context of cardiovascular diseases.